NEUTROPHIL FUNCTION (INNATE IMMUNITY) DURING RAMADAN - Latifynia, Afshineh; Vojgani, Mohammad; Gharagozlou, Mohammad Javad; Sharifian, R (Journal of Ayub Medical College Abbottabad, 2009)
Background: Fasting during the month of Ramadan is one of the essential religious practices of Muslims. The aim of this study was to evaluate opsonisation, phagocytosis, and nitroblue tetrazolium (NBT) reduction by white blood cells in normal, healthy, male subjects under nonfasting (before Ramadan) and fasting (after Ramadan) conditions. Methods: In this study, 13 Muslim men, aged 28-54 years, whose health was confirmed by health application forms, gave blood samples one week before the beginning of the holy month of Ramadan and during the last week of Ramadan. Blood samples were tested for neutrophil phagocytosis, serum opsonisation power, and NBT reduction. Results: Despite a decline in the neutrophil phagocytic index and serum opsonisation index, the percentage of neutrophils participating in phagocytosis increased with fasting. In addition, there was an increase in the percentage of neutrophils demonstrating NBT reduction. Although there was a decrease in opsonisation of the serum, the increased percentage of opsonisation compensated for this defect. Conclusion: This study demonstrates the beneficial effect of fasting during Ramadan on neutrophil phagocytic function. Keywords: Neutrophil, Ramadan, Nitroblue tetrazolium, Phagocytosis, Opsonisation